Anatomical variations in the extra hepatic biliary system: a cross sectional study - Anandhi, P. G.; Alagavenkatesan, V. N. (International Journal of Research in Medical Sciences, 2018)
Background: The anatomy of the biliary system has been the subject of extended research for many years. Largely because of their surgical importance in cholecystectomies and the ease with which they may be studied. Though, interest has been focused on the extrahepatic bile ducts very few studies have been carried out in the Indian subcontinent. Objectives was to study the anatomical variations in extrahepatic biliary system in sample of Indian cadaveric specimens. Methods: The study material consisted of 20 adult dissection room cadavers and 30 enbloc post-mortem specimens. Cadaver specimens were studied from dissection room. Post-mortem enbloc specimens were collected from the Department of Forensic Medicine, Madurai Medical College, Madurai. They were studied by conventional dissection method. Results: The key abnormalities found in all bladder were Hartman's pouch shape and neck in 2 (4%) subjects each. Gallstones were present in 2 (4%) subject. The length of the common Bile duct was ranging from as short as 6.5 cm in 24% of the subjects to 9cm in 4% of the subjects. High level of the cystic duct union with the common hepatic duct was noted in16% of specimens and in remaining 2% it was low union. Abnormal arrangement of structures in hepatoduodenal duct was normal in 98% but was abnormal in 2% of subjects. A total of 14% of the specimens had accessory ducts. Double and accessory cystic artery was found in 2% of the subjects each. In 8% of the subjects, cystic artery had abnormal course and division. The right hepatic artery was had shown abnormal course and division in 4% of the subjects. Abnormal boundaries of Calot’s triangle was found in 2% of the subjects. Abnormal contents of Calot’s triangle include Accessory hepatic ducts in 10% of subjects. Conclusions: Anatomical variations of the extrahepatic biliary system are very common and a through an understanding of them is essential for surgeons to avoid damage to vital structures during surgical procedures and better surgical outcomes.